Studies of GaN-on-GaN vertical Schottky diodes for radiation sensing applications - Sandupatla, Abhinay (Nanyang Technological University, 2020)
Gallium Nitride (GaN) with its large bandgap, high electron saturation velocity, and critical electric field has been widely applied in the fabrication of illumination, high frequency, and high-power devices. Recently, researchers are exploring radiation sensing as a probable application for GaN devices on the virtue of the high Displacement Energy (ED) of GaN (20 eV) which is twice higher than any other semiconductors such as GaAs and Si. Up till now, different research groups have successfully fabricated GaN Schottky Barrier Diodes (SBD) and tested them in alpha particle detection. While SBDs with thin epitaxial layers (<12 μm) could only detect low energy alpha particles (<4.5 MeV) at -120 V, SBDs on bulk GaN substrate required very high voltage (-550V) to detect higher energies (5.48 MeV). However, both bulk GaN SBDs and SBDs with thin epitaxial layers show extremely poor performance at low voltages. The poor performance of GaN-based radiation detector is due to high Threading Dislocation Density (TDD) and limited Depletion Width (DW). While high TDD increases leakage current (IR) thus reducing the sensitivity of the detector, thin DW restricts the maximum energy which can be detected by a GaN detector. In this thesis, the focus is to reduce IR and increase DW by reducing TDD, Charge Carrier Density (CCD), and increasing Drift Layer Thickness (DLT). While TDD was successfully reduced by employing a GaN-on-GaN structure, CCD was reduced by compensating the un-intentionally doped n-type (Si) dopants with p-type (Mg) dopants. In addition, multiple Drift Layers (DL) of different thicknesses were grown to study the impact on SBD performance. Finally, the fabricated SBDs were then tested as radiation detectors to detect 5.48 MeV alpha particles. In this work, the employment of GaN-on-GaN structure reduces the lattice and thermal expansion coefficient mismatch which in turn results in ~3 orders of magnitude reduction of TDD. Approximately 2 orders of magnitude reduction in CCD was successfully achieved by compensating the unintentional n-type (Si) dopants with p-type (Mg) dopants. The reduced CCD results in 3 orders of magnitude lower IR (3 pA) and ~3 times higher VBD (1480 V), while having minimal impact on the forward current-voltage characteristics. It was also found that compensation also results in a change of conduction mechanism from barrier modified Thermionic Field Emission (TFE) to regular TFE due to thicker DW. SBDs were fabricated on wafers with different DL thicknesses (2 μm, 5 μm, 15 μm, and 30 μm) to increase DW and enable high energy detection. While SBDs with thicker DL exhibited lower IR, it also reduced forward saturation current. A linear increase in VBD from 560 V to 2400 V, with an increase in DLT, was also observed. The measured VBD of 2400 V in SBDs with 30 μm DLT is by far the highest reported VBD. Increase of DLT has also resulted in a change of conduction mechanism from TFE to Thermionic Emission (TE) due to a reduced probability of tunnelling in thicker DLs. SBDs were tested for radiation sensing application by exposing them to Am-241 alpha particle source which releases 5.48 MeV alpha particles. These SBDs exhibited a near-ideal Charge Collection Efficiency (CCE) at 96% at -300 V. The detectors also exhibited 25% superior performance in low bias conditions (-20 V) with 3 times lower variation of efficiency as a function of applied voltage (-20 V to -80 V) in comparison with other reported GaN radiation detectors. In summary, high-energy alpha particle detection at low voltages have been demonstrated in this work with the employment of compensated GaN-on-GaN SBDs to reduce the TDD, CCD, and increase the DW. The designed GaN detectors exhibited high CCE (65%) even at low voltages (-20V) thus shows the feasibility to realize compact and portability GaN-based radiation detectors.